Functionality of endothelial cells differentiated from porcine epiblast stem cells, bone marrow-derived mesenchymal stem cells and adipose-derived mesenchymal stem cells - Yeon-Ji Lee; In-Won Lee; Tae-Suk Kim; Bo-Gyeong Seo; Sang-Ki Baek; Cheol Hwangbo; Joon-Hee Lee (Journal of Animal Reproduction and Biotechnology)
Background: Pluripotent stem cells (PSCs) are capable of differencing into various cell types in the body, providing them valuable for therapy of degenerative diseases. Patient-specific treatments using PSCs, such as mesenchymal stem cells in patient’s own body, may reduce the risk of immune rejection. Inducing the differentiation of PSCs into vascular endothelial cells (ECs) altering culture conditions or using specific growth factors is able to applied to the treatment of vascular diseases. The purpose of this study was to induce the differentiation of porcine epiblast stem cells (pEpiSCs), bone marrow-derived mesenchymal stem cells (pBM-MSCs) and adipose-derived mesenchymal stem cells (pA-MSCs) into ECs and then examine the functionality of vascular ECs. Methods: Porcine pEpiSCs, pBM-MSCs and pA-MSCs were induced to differentiate into ECs on matrigel-coated plates in differentiation medium (EBM-2 + 50 ng/mL of VEGF) for 8 days. Cells differentiated from these stem cells were isolated using CD-31 positive (+) magnetic-activated cell sorting (MACS) and then proliferated in M199 medium. Evaluation of ECs differentiated from these stem cells was treated with capillary-like structure formation and three-dimensional spheroid sprouting assay. Results: Porcine pEpiSCs, pBM-MSCs and pA-MSCs showed similar expression of pluripotency-related genes (OCT-3/4. NANOG, SOX2). These stem cells were differentiated into vascular ECs, but showed different morphologies after the differentiation. Cells differentiated from pEpiSCs showed an elongated spindle-like morphology, whereas cells differentiated from pBM-MSCs showed a round pebble-like morphology. In the case of pA-MSCs, these two morphologies were mixed with each other. Additionally, vascular ECs differentiated from these stem cells showed different formation of capillary-like structure formation and three-dimensional spheroid sprouting assay. Conclusions: Cells differentiated from pEpiSCs, pBM-MSCs and pA-MSCs presented the functionality of different vascular ECs, demonstrating the potential of the excellent ECs differentiated from pEpiSCs.